The Role Of Interactive Powerpoint In Student Participation - A. Nur Afifah Muhja; R. Rosdiana (Manunggal Halim Jaya, 2026)
This study aims to describe the implementation of interactive PowerPoint (PPT)-based learning media in the learning process and analyze the effect of its use on student participation and activeness. This study uses a qualitative approach with descriptive methods. The research subjects consisted of teachers and students from three schools, namely MAN 1 Baubau, SMA Negeri 3 Takalar, and MA Nurul Ikhwan Maros. Data collection was conducted through semi-structured interviews with teachers and students, as well as an open-ended questionnaire given to 20 students to determine their perceptions of the use of interactive PPT in learning. In addition, supporting data was obtained through literature studies from books, scientific journals, and relevant research articles. Data validity was tested using source triangulation and technical triangulation techniques, as well as member checking to ensure the data conformity with the informant's experience. The results show that the use of interactive PPT has a positive impact on the learning process. This media is able to increase student interest and motivation in learning, facilitate understanding of concepts, and encourage student participation and activeness during learning activities. However, the implementation of interactive PPT still faces several obstacles, especially limited technological facilities and differences in the level of digital literacy of teachers and students. Therefore, adequate support for facilities and infrastructure as well as improving teacher competence is very necessary so that the use of interactive PPT media can be optimized effectively in learning.